Outcome, Process & Power in Direct Democracy - Bruno S. Frey; Marcel Kucher; Alois Stutzer (Center for Economic Studies and ifo Institute (CESifo), 1999)
Based on survey data for Switzerland, new empirical findings on direct democracy are presented. In the first part, we show that, on average, public employees receive lower financial compensation under more direct democratic institutions. However, top bureaucrats are more constrained in direct de m ocracies and have to be compensated by higher wages for that loss of power. In the second part, we demonstrate that reported subjective well-being of the population is much higher in jurisdictions with stronger direct democratic rights. This is not only the case because people value political outcomes higher but they derive utility from the politcal process itself.
Keywords: 330; Direct democracy; power; compensating wage differentials; satisfaction with life; process utility